2014
DOI: 10.1021/bm501409n
|View full text |Cite
|
Sign up to set email alerts
|

Diverse Formulas for Spider Dragline Fibers Demonstrated by Molecular and Mechanical Characterization of Spitting Spider Silk

Abstract: Spider silks have outstanding mechanical properties. Most research has focused on dragline silk proteins (major ampullate spidroins, MaSps) from orb-weaving spiders. Using silk gland expression libraries from the haplogyne spider Scytodes thoracica, we discovered two novel spidroins (S. thoracica fibroin 1 and 2). The amino acid composition of S. thoracica silk glands and dragline fibers suggest that fibroin 1 is the major component of S. thoracica dragline silk. Fibroin 1 is dominated by glycine-alanine motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
(184 reference statements)
2
4
0
Order By: Relevance
“…Outside of Entelegynae, dragline silk sequences from the basal clades that include Hypochilidae and Haplogynae [ 33 ] largely did not conform to the MaSp1/MaSp2 consensus motif criteria identified in this study. Instead, the repetitive modules from the basal groups typically featured long and complex arrays of residues, consistent with a non-homologous origin of MaSps between the basal and entelegyne taxa, as proposed [ 4 , 12 , 47 , 48 ]. However, one sequence from H .…”
Section: Resultssupporting
confidence: 72%
“…Outside of Entelegynae, dragline silk sequences from the basal clades that include Hypochilidae and Haplogynae [ 33 ] largely did not conform to the MaSp1/MaSp2 consensus motif criteria identified in this study. Instead, the repetitive modules from the basal groups typically featured long and complex arrays of residues, consistent with a non-homologous origin of MaSps between the basal and entelegyne taxa, as proposed [ 4 , 12 , 47 , 48 ]. However, one sequence from H .…”
Section: Resultssupporting
confidence: 72%
“…Most of the spidroin contigs identified in this study (except for the tubuliform spidroin) contain novel combinations of amino acid sequence motifs that have not been observed before in these spidroin types ( S2 Fig ). The grouping of ampullate spidroins within a diverse ampullate clade has also been observed in other analyses of spidroin C-termini [ 44 , 55 ]. Relationships among ampullate spidroins within and across species are complicated, suggesting turnover (birth, death) and/or sequence conversion [ 31 , 32 , 56 – 58 ].…”
Section: Discussionsupporting
confidence: 69%
“…Pioneering work by Gatesy et al (14) identified and analyzed spidroin sequences from several spider lineages, including basal spider groups, thus enabling a glimpse into the complex evolution of spidroin sequences. Subsequently, there have been a large number of studies that have explored the subject of spidroin sequence diversity and evolution, including focused studies on various spidroin paralogs (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29), and those from more phylogenetic perspective (7,(30)(31)(32)(33)(34), predominantly based on the conserved terminal sequences. On the other hand, the mechanical properties of silk fibers are governed largely through the repetitive regions that dominate the silk protein sequence, and the study on the diversity of spidroin repetitive regions, particularly in the more evolutionarily divergent taxa, has been limited to date.…”
Section: Introductionmentioning
confidence: 99%